AN ANALYSIS OF STUDENTS’ ERRORS IN WRITING OF RECOUNT A Case Study at the Eleventh grade MIPA2 of SMA Neg. 1 Tongauna Academic Year 2020/2021 - M. Fadli (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The aims of this study were in term of construct the recount text, the use of correct grammar was need to mastery by the students. In the eleventh grade of SMA Neg. 1 Tongauna, in which this study was conducted to analyze of error students’ in writing of recount text. This study was descriptive analysis method in form of qualitative research. The sources of the study were the students from eleventh grade of MIPA2 that consisted of 28 students, but the researcher only analyzed 20 students. The instrument used in this study was writing text, the students made a recount text. In collecting data, students were giving the writing test of recount text. The data of students writing text showed the types of errors that students made in recount text. From the type of errors the researcher just focused in misformatioan and misordering based on surface strategy taxonomy. In misformation errors there three types, those are regularization error, archi form, and alternating form. The types of errors made by the students were 205 errors or 101,90%, misformation were 182 errors or 90,77% with categories regularization errors were 8 errors or 3,90%, archi form 55 errors or 26,83%, and alternating form were 119 errors or 58,05%. In misordering were 23 errors or 11,22%. Based on the result of this study, the researcher concluded that the dominant errors made by the students were alternating form of misformation as a highest level of the errors.